Réponses

2013-10-15T14:18:15+02:00
3) A = 5/7 - 2/7 x 4/3 = 5/7 - 8/21 = 15/21 - 8/21 = 7/21 = 1/3
4) B = (4x + 3)(7x -2) = 28 x^2 - 8x + 21x - 6 = 28 x^2 + 13 x - 6
5) C = (6 x 10^-2 x 15 x 10^17)/(8 x 10^2) = ((6 x 15)/8) x ((10^-2 x 10^17) x 10^2) = 11,25 10^13 = 1,125 x 10^14
2013-10-15T16:10:37+02:00
A = 5/7 - 2/7 X 4/3 = 5/7 - 8/21 = 15/21 - 8/21 = 7/21 = 1/3
B = (4x + 3)(7x -2)
28 x² - 8x + 21x - 6 
28 x² + 13 x - 6
C = (6 x 10P-2 x 15 x 10P17)   Ici, tu multiplies les entiers entre eux puis les P10
        (8 x 10P2)
6 x 15 X 10 P-2+17 = 90 X 10 P 15 -2 = 11,25 X 10 P 13 = 1,125 X 10 P14
8 X 10 P2                  8